Inhibition of α-glucosidase Activity Seed Extract from Mahogany (Swietenia macrophylla King.) - Waras Nurcholis; Rini Muthoharoh; Antonius Padua Ratu (IPB University, 2019)
Diabetes mellitus is a chronic disorder that affects the metabolism of blood glucose inside the body. One of the alternative treatments is by using traditional medicinal plants, which have hypoglycemia effects. A mahogany seed is one of the traditional medicinal plants that has been proven to treat diabetes and has been used for generations. In the aqueous extract, ethanol 96 %, ethyl acetate, and hexane from mahogany seeds (Swietenia macrophylla King.) the inhibition of α-glucosidase activity are checked by measuring p-nitrophenol from p-nitrophenyl-α-D-glucopyranose (pNPG) on 400 nm. The percentage value of the inhibition for α-glucosidase ranged from 6,36-56,77 %, with 96 % ethanol extract that has the highest value and the hexane extract with the lowest value. Phytochemical screening revealed the presence of alkaloids, flavonoids, saponins, and triterpenoids, which could be responsible for the bioactivities shown by the 96 % ethanol extract and aqueous extract of S. macrophylla. Keywords : α-glucosidase activity, diabetes mellitus, mahogany seeds (Swietenia macrophylla King.), phytochemical screening.